Effects of air intake pressure to the fuel economy and exhaust emissions on a small SI engine - Nik Rosli, Abdullah; Nafis Syabil, Shahruddin; Aman Mohd. Ihsan, Mamat; Salmiah, Kasolang; Aminuddin, Zulkifli; R., Mamat (Elsevier Ltd, 2013)
This study discusses on the fuel economy and exhaust emissions at variations of air intake pressure. The air intake pressure is influenced by the degree of opening throttle plate and venturi effect which draw the fuel to the combustion chamber in carbureted engine. The experimental work is conducted at variations of engine speed and load using a single cylinder four stroke SI engine attached with 5 kW dynamometer. Gas analyzer was used to measure exhaust emissions compositions and to identify the quality of combustion. The results show that the standard air intake system resulted in rich combustion which led to the incomplete combustion due to less availability of air. By eliminating the air filter, the air flow restriction through the air intake system was reduced. Hence, better combustion and less unburned components are achieved because of higher air availability. A higher air intake pressure is required to increase air density in allowing for better combustion within a limited time to improve fuel economy, power output and exhaust emissions. Complete combustion also lead to the reduction of unburned components such as carbon (C), hydrogen (H2), carbon monoxide (CO) and hydroxide (OH) that resulted in less hazardous emissions.